COVID-19 and Acute Lupus Pneumonitis: Diagnostic and Treatment Dilemma. (June 2020) - Kichloo, Asim; Aljadah, Michael; Albosta, Michael; Wani, Farah; Singh, Jagmeet; Solanki, Shantanu
In this article, we present a case of a young female patient with previously diagnosed lupus pneumonitis, now with a flare and new superimposed COVID-19 infection that was treated with intravenous steroids. On computed tomography scans, she had extensive interstitial lung fibrosis in addition to a positive COVID-19 polymerase chain reaction test requiring 6 L of oxygen via nasal cannula on admission. After administration of methylprednisolone, the patient improved and was weaned off her oxygen requirements and was discharged home.